2017
DOI: 10.1093/ecco-jcc/jjx110
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification for Surgery in Stricturing Ileal Crohn’s Disease: The BACARDI Risk Model

Abstract: This risk model can facilitate therapeutic decisions in IS-CD and suggest the correct time for surgery in daily clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
1
21
1
2
Order By: Relevance
“…The success rate of these EBD procedures was 84%, and the long-term prevention of surgery following EBD was 67.2%. These findings in agreement with success rates, [6,10,11] and surgery free survival [1214] reported by others. Two recent meta-analyses reported an 89% technical success rate of EBD procedures among CD patients.…”
Section: Discussionsupporting
confidence: 92%
“…The success rate of these EBD procedures was 84%, and the long-term prevention of surgery following EBD was 67.2%. These findings in agreement with success rates, [6,10,11] and surgery free survival [1214] reported by others. Two recent meta-analyses reported an 89% technical success rate of EBD procedures among CD patients.…”
Section: Discussionsupporting
confidence: 92%
“…In general, the behavior of CD at diagnosis has been identified as an independent risk factor for early surgery. Particularly, in ileal CD with stricture, prestenotic dilatation, CRP, combined penetrating behavior, exposure to biologics, and presence of NOD2 rs2066844 risk allele are all significantly associated with an increased risk of surgery [33]. However, no study has been performed using machine learning techniques to develop prediction models regarding surgery risk using combined clinical and genetic data.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that stricturing Crohn's disease is associated with a high morbidity, with almost half (46%) of all patients having surgery, often within a few months of stricture diagnosis. Historic cohorts, with strictures identified using a variety of techniques and with variable follow‐up, have reported a 50–70% surgical rate over 10 years …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Bossuyt et al . developed the “BACARDI” risk model for stratifying patients with Crohn's strictures . This model included clinical, radiological, and genetic risk factors.…”
Section: Discussionmentioning
confidence: 99%